Review and Bibliometric Analysis of Biogas Power Plants in Indonesia - Dhasa Ikrar Setyanansyach; Muji Setiyo; Thirunavukkarasu Raja (Advance Sustainable Science Engineering and Technology, 2023)
The demand for energy is increasing due to population growth, technological advancements, and a growing need for sustainable energy sources. Indonesia, which faces an energy deficit, is exploring alternatives to fossil fuels. Biogas, produced through the anaerobic fermentation of organic matter, offers a clean and sustainable energy option while addressing waste disposal issues. Therefore, this literature review examines various aspects of a biogas power plant, including a feasibility study that encompasses technical and economic analyses, generator design, trials, implementation, and post-implementation evaluation. In this review, we gathered scientific papers from Google Scholar using the keywords "pembangkit listrik biogas" between 2019 and 2022, with a focus on recent content. Patents and citations were excluded from the Google Scholar searches to ensure article relevance. Out of a total of 40 articles, 30 were rejected because they did not originate from scientific journals. The collected articles are categorized based on the materials used for biogas generation in power plants. This systematic approach yielded 10 relevant articles. Consequently, the literature reveals that various raw materials, such as palm oil mill waste (POME), livestock manure, and organic waste, hold the potential for biogas production. The results emphasize the economic feasibility of specific biogas projects, the environmental challenges they pose, and the positive impact they have on community well-being